Love again [videorecording (DVD)] - Strouse, James C. (James Clifton), 1977-; Chopra Jonas, Priyanka; Heughan, Sam, 1980-; Dion, Céline; Tovey, Russell; Oram, Steve, 1973-; Kene, Arinze; West, Lydia (Actor); Barclay, Sofia; Imrie, Celia, 1952-; Djalili, Omid, 1965-; Cramer, Sofie, 1974- (Sony Pictures Home Entertainment, 2023)
Dealing with the loss of her fiancé, Mira Ray sends a series of romantic texts to his old cell phone number...not realizing the number was reassigned to Rob Burns' new work phone. A journalist, Rob is captivated by the honesty in the beautifully confessional texts. When he's assigned to write a profile of megastar Celine Dion, he enlists her help in figuring out how to meet Mira in person...and win her heart.